Pendidikan Kewarganegaraan Pada Generasi Alpha Sebagai Upaya Membangun Kesadaran Kewarganegaraan Yang Berkualitas - Ghina Salsabila, Oktaviani; Maulana, Nicholas; Syahputra, Muhammad Rikky; Hasanah, Mutia; Hudi, Ilham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Civic education in the Alpha generation is important as an effort to build quality civic awareness. Generation Alpha, born at the beginning of the 21st century, grew up in a globally connected digital era. This abstract explores the role of citizenship education in shaping their understanding of democratic values, political participation, human rights, and cultural pluralism. By strengthening their awareness of their responsibilities as citizens, citizenship education can help them become agents of positive change in society. An innovative and technology-based educational approach is needed to reach the Alpha generation effectively. An emphasis on intergenerational collaboration, critical thinking, and problem-solving will help create an Alpha generation that is skilled, educated, and caring about a complex global society